Corporate social responsibility reporting in the hotel industry - Krambia-Kapardis, Maria; Neophytidou, Christina (My University, 2014)
Global trends in the field of Corporate Social Responsibility (CSR) such as the welfare of employees and the shortage of natural resources, along with technological innovations have all resulted in a new set of stakeholder requirements. Stakeholders are nowadays demanding not only for sustainable products and/or services, but also require the corporations behind the brands they are consuming to offer greater transparency and reveal their accountability with regards to the way they carry out business. Consequently, to meet the needs of stakeholders, many corporations have already incorporated the sustainability discourse in their business strategies. More recently, corporations have started to publish sustainability reports, as a means of informing their stakeholders and shareholders about their organizations’ environmental and social performance. Previous studies within the hospitality sector, indeed confirm that hoteliers have already started to incorporate CSR and the reporting practise in their businesses, as they have documented an increase in sustainability reporting in the hotel sector over the past few years. Evidence suggests that by incorporating sustainability in their business strategies, hotels can decrease their operating costs, differentiate their product, and enhance their brands’ image. In addition, by drafting sustainability reports to comment upon these issues, hotels can attract more customers, provide better hospitality products, assist in the formation of sustainable tourism destinations, and improve their overall performance efficiency. The paper reaches the conclusion that sustainability reporting within the hotel sector will gain more momentum in the near future as it will become a valuable tool for gaining a competitive advantage With this in mind, the purpose of the paper is to explore the notion of CSR within the hotel industry and to document the benefits derived by the reporting practise. For the purposes of the paper, the researchers will review existing literature in the field of CSR, sustainability and sustainability reporting in the hotel industry and retrieve data regarding the environmental and social performance from the hotels’ corporate websites.
Keywords: corporate social responsibility; sustainability; sustainability reporting; hotel industry